The puffin keeper - Morpurgo, Michael (Puffin, 2022)
Allen Williams was rescued by a lighthouse keeper named Benjamin Postlethwaite when he was five years old. Years later, Allen returns to meet the man who saved his life and winds up staying to help rescue an injured puffin, the first on Puffin Island in over a century. Allen is forced to leave once more when he is called to fight in World War II but later returns to make a home on the island.